2020
DOI: 10.7739/jkafn.2020.27.3.298
|View full text |Cite
|
Sign up to set email alerts
|

Unmet Needs for Job Maintenance of Breast Cancer Survivors

Abstract: Purpose: To develop and apply an integrative model for breast cancer survivors’ return to work, survivors’ unsatisfied demands for job maintenance were identified.Methods: This study was a qualitative research that used a focus group to investigate breast cancer survivors’ unsatisfied demands for job maintenance. Data collection was conducted four times from February to October 2019 with six participants.Results: The study showed that the six participants identified the following unsatisfied demands for breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Conversely, religious well‐being is distinguished as well‐being based on religion, such as a relationship with God and religious coping 24 . A previous study reported that high spiritual well‐being generally contributed to the maintenance of physical and mental health, as well as functional status of female cancer survivors 6,23,25 . To our knowledge, there are few studies in South Korea to investigate the factors that influenced distress in working female cancer survivors 6,16,20 .…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…Conversely, religious well‐being is distinguished as well‐being based on religion, such as a relationship with God and religious coping 24 . A previous study reported that high spiritual well‐being generally contributed to the maintenance of physical and mental health, as well as functional status of female cancer survivors 6,23,25 . To our knowledge, there are few studies in South Korea to investigate the factors that influenced distress in working female cancer survivors 6,16,20 .…”
Section: Introductionmentioning
confidence: 96%
“…Due to this high survival rate, female cancer survivors require long‐term management to improve their quality of life because they also have a higher incidence of post‐traumatic stress following cancer diagnoses than men, along with increased levels of anxiety regarding recurrences with longer survival periods 3–5 . Therefore, to manage the long‐term quality of life, economic stability is necessary and personal, societal awareness, and interest regarding cancer survivors' return to work have been rising 6,7 . Distress is one of the major factors affecting the quality of life of female cancer survivors, with 42.1% of cancer survivors experiencing distress related to cancer diagnosis and treatments in South Korea, which is higher than in the United States and Canada 8 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations